Archean granitoid magmatism in the Canaã dos Carajás area: implications for crustal evolution of the Carajás province, Amazonian Craton, Brazil - Feio, Gilmara Regina Lima (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
Teses e dissertações